Improving the Skills of Farmers and Women Farmers Groups in Belantih Village, Bangli, in Making Waste-Based Organic Fertilizer - Astiari, Ni Komang Alit; Suaria, I Nengah; Singapurwa, Ni Made Ayu Suardani; Sutapa, I Gede; Andriani, Agung Sagung Putri Risa; Rama, Kade Nusde Sari; Saputra, Arya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community service initiative, conducted on June 21, 2025, addressed the dual challenges of inorganic fertilizer scarcity and environmental pollution in Belantih Village, Bangli. The program aimed to empower the Dharma Kriya and Widya Pertiwi farmer groups by enhancing their skills in converting organic waste into valuable solid and liquid fertilizers. The activity employed a hands-on training methodology, which included a theoretical session followed by practical implementation and a final evaluation. The findings revealed a significant increase in participant knowledge, with 95% of respondents reporting a comprehensive understanding of the material and methods, and the remaining 5% reporting a good grasp. All 20 participants expressed a strong desire to adopt the new skills. Specifically, 80% expressed high satisfaction and interest in applying the techniques to improve the quality of their intercropped citrus and coffee plants. In comparison, the remaining 20% were eager to implement the process for personal use. This project successfully demonstrated that a practical, hands-on approach can effectively transfer knowledge and motivate community members to embrace sustainable practices. The adoption of these waste-processing techniques provides a viable and environmentally friendly solution for mitigating fertilizer shortages while simultaneously enhancing agricultural productivity and reducing pollution. Contribution to Sustainable Development Goals (SDGs):SDG 2 -Zero HungerSDG 12 Responsible Consumption and ProductionSDG 13 Climate ActionSDG 15 Life on Land